Five Principles of Philosophical Health for Critical Times: From Hadot to Crealectics - de Miranda, Luis (Eidos. A Journal for Philosophy of Culture, 2021)
In a world described or experienced as unfair, what can philosophical practitioners propose in order to help individuals and communities strive for a meaningful life? One answer, empirically informed by the author’s practice as philosophical counselor in therapeutic, self-care and organizational contexts, is five principles for the cultivation of philosophical health, namely mental heroism, deep orientation, critical creativity, deep listening, and the “Creal” (the creative Real as ultimate possibility). In the light of Hadot’s rediscovery of philosophy as a way of life and in dialogue with his reading of ancient philosophy, it is asserted that the embodied and socially embedded mind can, through these five principles or modalities, be prepared to maintain a pragmatic elevation of view and creative resilience in everyday events, especially in critical situations. This meta-analytic and meta-dialectic practice of philosophical health, termed “crealectics,” presupposes that we are of the same creative cosmological flesh (the Creal), and therefore we are bound to comprehend and care for each other philosophically.